The Influence Of Pregnant Women's Class On The Anxiety Of Primigravida Mothers In Kabanjahe Health Center, Kaban Jahe District, Karo District, 2023 - Sinaga, Lenni Ida Wati Br.; Eva Ratna Dewi; Marliani; Agussamad, Indra; Nurhalija, Siti (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2023)
The Pregnant Women Class is a study group for pregnant women with a gestational age between 4 weeks to 36 weeks (before delivery) with a maximum number of participants of 10 people. The aim of this research is to determine the influence of the Pregnancy Class on Primigravida Mothers' Anxiety at the Kabanjahe Community Health Center in 2023. This research is quantitative research. This research uses correlational research. Population is the subject of research. The population in this study were all primigravida mothers with a gestational age of 8-37 weeks, namely 30 people. The research sample and the sampling technique used a total sampling technique, namely 30 people, so the entire population was used as the research sample. The time period required for this research is April to July 2023. The location of this research will be carried out at the Kabanjahe Community Health Center, Kabanjahe District, Karo Regency in 2023. This analysis was carried out to see the relationship between the independent variable (class of pregnant women) and the dependent variable (level of maternal anxiety primigravida). Does this variable have a significant relationship. In this analysis the statistical test used is the Chi Square test with a significant p-value (0.05). The results of the Spearman correlation analysis showed that there was a significant correlation between the class of pregnant women and primigravida anxiety with P = 0.010 with a strong correlation coefficient value between the class of pregnant women and the anxiety of primigravida mothers. If the class variable for pregnant women increased then the anxiety variable for primigravida mothers decreased and conversely, if the class variable for pregnant women decreases, the anxiety variable for primigravida mothers increases. Keywords: Pregnant women's class, pregnancy, anxiety, primigravida